Integration of inbrigin, inheritance and environment in islamic educational psychology on the establishment and caring of children's character - Nasrullah, Muhammad; Tuanto, Eko (CAHAYA PENDIDIKAN, 2023)
Basically, humans are born with a good nature, so humans naturally do not do bad things. However, in reality, there is more and more news about crimes both among living beings and with nature. Behavior that deviates from human nature certainly does not just happen without any causal factors, many factors cause changes in human character, starting from family, environment, educators and so on. So that there is a need for efforts to shape and care for one's character from an early age in terms of an Islamic psychological approach. This research is a qualitative research using literature review method to collect relevant data. Then the data is analyzed using the content analysis method or content analysis. The results of the study show that character building must start early from the family environment, school to the community. This must be done continuously so that the good character of the child is maintained until the end of life as a form of human implementation as the best creation of Allah SWT.